Larval masquerade: a new species of paedomorphic salamander (Caudata: Plethodontidae: Eurycea) from the Ouachita Mountains of North America - Steffen, Michael A.; Irwin, Kelly J.; Blair, Andrea L.; Bonett, Ronald M. (Zootaxa, 2014)
Species with truncated developmental patterns may go undetected if they resemble the juveniles of their close relatives. Herein we present an example of this phenomenon with the description of a highly divergent, relict species of stream-dwelling plethodontid salamander from the Ouachita Mountains of North America. Both mitochondrial and nuclear sequence data show that this new species is most closely related to its syntopic relative, Eurycea multiplicata. Interestingly, E. multiplicata exhibits the ancestral biphasic (metamorphic) life cycle, whereas the new species maintains an aquatic larval form throughout life (paedomorphic) and superficially resembles larval E. multiplicata. The new species is the first known paedomorphic plethodontid from the Ouachita Mountains, and the most divergent paedomorphic salamander discovered in over seventy years. This species represents an independent instance of the evolution of paedomorphosis associated with a porous streambed, which may facilitate vertical seasonal movements. This new species currently has an extremely limited known distribution and is of immediate conservation concern.